Atomic hydrogen adsorption and desorption on/from graphite via the armchair edge: A quantum dynamic study - Natividad, Michelle T. (Animo Repository, 2013)
This study investigates the quantum mechanical behavior of the adsorption and desorption of hydrogen atom on/from graphitevia the armchair edge. The adsorption and desorption probabilities of H are calculated using the coupled channel method via the Local Reflection (LORE) matrix and are plottedagainst the initial translational energy of H. The adsorption probability plot shows a non-activated reaction indicating that hydrogen is easily adsorbed on the surfaceof the graphite sheets. On the other hand, the desorption probability plot shows that desorption of H from the graphic sheets is an activated process with a barrier height of 4.19 eV. Due to this high barrier, desorption of the adsorbed H atom from the surface of the graphite sheets at operating temperatures (300-1500 K) of conventional fuel cells is unlikely to occur.